The examination of ecosystem valuation using revealed preference approach - Kerpely , Klára; Horváth, Bálint; Bakosné Böröcz, Mária (Studia Mundi – Economica, 2016)
According to the current European and global trends the consideration of environmental values in decision making processes is turning to be a more and more significant aspect in political level. The number of the ecosystem valuation cases is highly increasing and the application surface for the certain methodologies includes local, national and global level examinations as well. Our research aims to discover a broader horizon of social and economic values of a project which targeted environmental improvement in the first place. The present paper introduces a case study for the economic valuation of natural capital through revealed preference methodology. The subject of the examination is an actual project concerning the revitalization of the Szabadság Island side branch of the Danube near Mohács.